THE OPTIMIZATION OF REINFORCING STEEL BY IRON FIBER (LATHE WASTE) AND OFFSET TECHNIQUE AT THREE-DIMENSIONAL PORTAL - Samuel Layang; Wiratno (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2015)
The objective of this study is to determine the effect of metal fibres (lathe waste) usages and offset technique at three-dimensional portals to the reinforcement wide. The study was conducting by experimental in laboratory. This experiment is arranged by testing of 25 cylindrical concretes (size 15 cm x 30 cm) under mix design method of SNI 03-2834-2000 (The procedure of making a normal concrete mix plan). All concrete cylinders were tested at 28 days of age in order to obtain an actual compressive strength. The ultimate moment capacity of three-dimensional portal is analyzed by STAAD Pro 2004 engineering computer program. The results of test shows that the compressive strength on concrete with 8% steel fibres is increased up to 45.46%. And the reinforcement wide were decresing up to 1.87% (pedestal level 1); 2.95% (pedestal level 2); 2.67% (field level 1) and 3.99% (field level 2). The beams which only using the offset technique will save the use of steel amounted to 17.81% (pedestal level 1); 18.25% (pedestal level 2); 2.38% (field level 1) and 2.80% (field level 2). Beams that used iron fibres and the offset technique will save the use of steel amounted to 18.25% (pedestal level 1); 20.18% (pedestal level 2); 4.92% (field level 1) and 6.55% (field level 2). Its decresing wide was showing on statics analisys and caculation of reforcing steel requirement.